(untitled) (Third Sector Social Economic Review, 2019)
SME’s constitute basis for both Turkey’s and other countries’ economy. The employment rate in our country, economy, contributions and play an important role in export shares. This study contains two steps. For the first step description, characteristics and place in the national economy of SME’s and problems of marketing, production, financial, personal etc are reviewed. For the second step production and marketing problems of Medical Cluster Companies located in Ostim region in Ankara were tried to collect with survey sheets. To determine problems of medical sector companies in Ostim region in Ankara, 43 survey sheets were sent to companies to determine research data.Data obtained via survey sheets were analyzed by MS. Excel and SPSS 19. Result of this analysis common production and marketing problems were determined.. Solution suggestions of these problems are also given.